(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Article is devoted to learning a second language and its acquisition in the educational-professional and extraoccupational colloquial fields of communication. The author considers the two points of view on the acquisition of language. According to the author, the distinction between explicit / implicit, «learned» / «acquired,» automatic / controlled information processing can be discussed in respect extraoccupational colloquial fields, talking about mastering of a second language in general (outside the scope of its use) is not correct. Differences in learning the language in everyday, household, educational and professional spheres are linked primarily to the definition of its methodological role in these areas. In extraoccupational colloquial fields the language is used primarily as a means of communication, and in the educational and professional its role as a means of scientific knowledge is highlighted.